PENGARUH INTERNAL MARKETING TERHADAP ORGANIZATIONAL PERFORMANCE DI ERHA CLINIC DENGAN MARKET ORIENTATION SEBAGAI VARIABEL INTERVENING - Ginting, Eva Valentina; Hati, Shinta Wahyu (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2020)
This study aims to determine and analyze how the influence of internal marketing to organizational performance in ERHA Clinic with market orientation as intervening variable. The type of research used is quantitative research with saturated sampling technique or examine the total population amounted to 60 people as many as 30 employees of ERHA Clinic Batam and 30 employees of ERHA Clinic Medan. The respondents consisted of staff working in Pharmacy, Frontliner, Nurse, Therapist, Medical Record, and all staff working in the Back Office unit. Data processing method using path analysis with SPSS 20 software.Â Based on the results of research stated that (1) internal marketing positively significant to market orientation in ERHA Clinic Sig. 0.000 (<0,05), (2) market orientation have positive and significant influence to organizational performance in ERHA Clinic Sig. 0,000 (<0,05), and (3) internal marketing have positive and significant effect to organizational performance in ERHA Clinic Sig. 0,000 (<0.05). This means that internal marketing affects organizational performance in ERHA Clinic.Â